Molecular Docking of the Interaction between Citrus amblycarpa Extract Contents and Inflammatory Proteins of Hepatic Steatosis - Rosida, Lena; Pratiwi, Dewi Indah Noviana; Panghiyangani, Roselina; Utami, Juliyatin Putri; Idhafi, Nasrul; Febriansyah, Muhammad; Budiarman, Andi Azizah Maulidia (Makara Journal of Science, 2024)
Citrus amblycarpa possesses various pharmacological activities, such as antioxidant, anticancer, antitumor, hepatoprotective, anti-inflammatory, antidiabetic, antiviral, antibacterial, and antifungal. The main active compounds in C. amblycarpa (including gamma (γ)-aminobutyric acid [GABA], hesperidin, naringin, neoeriocitrin, poncirin, quercetin, and rutin) show potential to interact with the inflammatory proteins in hepatic steatosis (such as nuclear factor kappa beta [NF-kB], tumor necrosis alpha [TNF-alpha], interleukin-6 [IL-6], c-Jun NH2-terminal kinase [JNK], and adiponectin). Molecular docking simulations were performed using Swiss Dock (http://www.swissdock.ch/), and analysis and visualization were conducted using Discovery Studio 4.1. Rutin, poncirin, hesperidin, and neoeriocitrin exhibit high affinities to NF-κB, TNF-alpha, IL-6, and adiponectin proteins, respectively. Similar to curcumin–adiponectin complex interaction, neoeriocitrin–adiponectin interaction involves GLY 223, PRO41, and VAL93 residues. Thus, the most potent inhibitor of hepatic sterosis marker was neoeriocitrin.